Process modeling and simulation of distributed parameter using (Mpdx) method with approximating solutions - Sas, Diana Monica; Unguresan, Mihaela-Ligia; Colosi, Tiberiu; Secara, Mihai (2014 IEEE International Conference on Automation, Quality and Testing, Robotics, 2014)
This paper presents a control system where the controlled plant is a distributed parameter process. Numerical simulation of the control system is accomplished using the method of Matrix of Partial Derivatives of the State Vector ( M pdx) associated with Taylor Series. By including a process modeled by a partial differential equation of second order with two independent variables, this presents (M pdx ) method with approximate solutions, which are needed to ensure the start of the calculations and to check the results.